Malaysia Automotive Industry: Moving Toward Energy Efficient Vehicle Era - Shukor, Muhamad Syakir; Sulaiman, Zuraidah; Thoo, Ai Chin; Mas’od, Adaviah (School of Social Sciences, USM, 2017)
Throughout the globe, humankind is facing several environmental problems such as climate change, resources depletion loss of biodiversity and much more. Transportation has become one of the important human essentials and among the major contributors to the overall environment degradation. To overcome these issues, both international and interdisciplinary measures needs to be implemented. Beginning 2014, national car producers have launched the Energy Efficient Vehicle (EEV) in an effort to react on both the declining environmental and fluctuating economical scenarios. Thus, this paper provides insights and reviews on the automotive market for ASEAN and Malaysia today. There is an increasing awareness by car producers and governments on the impacts of EEV; hence, actions have been make to promote Malaysia to become ASEAN regional EEV hub.